Evaluating the budgetary reliability of design stage elemental cost plan in building procurement: a New Zealand study - Adafin, J; Wilkinson, SJ; Rotimi, JOB; Odeyinka, HA (Department of Construction Economics and Management University of Cape Town, Cape Town, South Africa, 2016)
Accurate prediction of final tender sums (contract sums) of building projects depends on reliable projections of baseline cost plans developed at the design development stage. However, no matter how much care and effort is put into the preparation of design stage elemental cost plans, deviations are usually observed between these cost plans and the final tender sum. This makes accurate predictions challenging for construction practitioners in New Zealand. The major attributable factors for the observed variability are inherent risks in the design stage elemental cost plan development. Whilst this is recognised, this study evaluates the reliability of elemental cost plans in traditional building procurement. The study seeks to answer the question: is elemental cost plan a reliable budgetary tool for construction projects? The study was undertaken based on 20 completed building projects from which secondary data were collected within the New Zealand construction industry. Data analysis was carried out using document analysis and percentage deviation of final tender sums from the cost plans. Further analyses were carried out using root mean square and relative mean absolute deviation methods of analyses. The results showed that the budgetary reliability of elemental cost plans varied depending on project types. Whilst a deviation of -3.67% and +3.95% was obtained on the residential projects analysed, the deviation on educational projects was between -3.98% and +12.15%. Commercial projects attracted -14.22% and +16.33% while in the case of refurbishment projects, a deviation of -10.07% and +30.14% was obtained. These findings suggest that the larger or more complex a project is, the less reliable it is to use elemental cost plans to guarantee cost certainty.
Keywords: Elemental cost plan; Final tender sum; New Zealand; Reliability; Traditional building procurement